TRANSFORMASI PERTANIAN 4.0: MENGUKUR DAMPAK INVESTASI SOSIAL MELALUI PENDEKATAN SROI - Dian Felani Kesa; Gancar Candra Premananto (Halu Oleo University, 2023)
This research was conducted with the aim of finding out the impact of Creating Shared Value (CSV) activities carried out by the MM UNAIR 58 regular class on the community in Surabaya and encouraging the acceleration of Indonesia's agricultural development in the Digital Era. The approach used in this research is Social Return On Investment (SROI). The data used is in the form of data that has a clear quantitative value and can be measured in financial terms such as rupiah, while other data are assumptions that are monetized using standard document references, research output, community consensus and so on. The results of this study indicate that the ratio resulting from this CSV activity is high and has a large impact on world investment.